Technology, Learning, and Long Run Economic Growth in Leading and Lagging Regions - Amit Batabyal; Peter Nijkamp (European Regional Science Association (ERSA), 2014)
We use a dynamic model to study the effects of technology and learning on the long run economic growth rates of a leading and a lagging region. New technologies are developed in the leading region but technological improvements in the lagging region are the result of learning from the leading region's technologies. Our analysis sheds light on four salient questions. First, we determine the long run growth rate of output per human capital unit in the leading region. Second, we define a lagging to leading region technology ratio, study its stability properties, and then use this ratio to ascertain the long run growth rate of output per human capital unit in the lagging region. Third, for specific parameter values, we analyze the ratio of output per human capital unit in the lagging region to output per human capital unit in the leading region when both regions have converged to their balanced growth paths. Finally, we discuss the policy implications of our analysis and then offer suggestions for extending the research described here.
Keywords: R11; R58; O33; 330; Economic Growth; Lagging Region; Leading Region; Learning; Technology